-(3x-3)-(2x-5)+4=-5(x1)-(3x+2)+3

Simple and best practice solution for -(3x-3)-(2x-5)+4=-5(x1)-(3x+2)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3x-3)-(2x-5)+4=-5(x1)-(3x+2)+3 equation:



-(3x-3)-(2x-5)+4=-5(x1)-(3x+2)+3
We move all terms to the left:
-(3x-3)-(2x-5)+4-(-5(x1)-(3x+2)+3)=0
We get rid of parentheses
-3x-2x-(-5x1-(3x+2)+3)+3+5+4=0
We calculate terms in parentheses: -(-5x1-(3x+2)+3), so:
-5x1-(3x+2)+3
We add all the numbers together, and all the variables
-5x-(3x+2)+3
We get rid of parentheses
-5x-3x-2+3
We add all the numbers together, and all the variables
-8x+1
Back to the equation:
-(-8x+1)
We add all the numbers together, and all the variables
-5x-(-8x+1)+12=0
We get rid of parentheses
-5x+8x-1+12=0
We add all the numbers together, and all the variables
3x+11=0
We move all terms containing x to the left, all other terms to the right
3x=-11
x=-11/3
x=-3+2/3

See similar equations:

| -11+11n=-121 | | 25=r+2+2r-13 | | X+5=2x-24=180 | | 7=-3+2a | | 2(3x-4)=-8-6x) | | 4.3x-7.95=2.8 | | -(8m+8)=-16 | | -5y÷3+3=8 | | 2/3​(3x+9)=−2(2x+6)​ | | 5h-4h+3h-4h+2h=12 | | 7x-5(x-4)=18 | | y=-54 | | 1.25((4x-10)=7.5 | | 3(5x+10)=12x-3 | | 0.6x=1.2-x | | 17x-35+11=180 | | 23-13x=-22.5 | | 5n+2(4n-3)=-2 | | 6x+3=21=8x-1=17 | | 3x+17=6x+1 | | 2y-2=4(y-2) | | 6-7k=-8k-1 | | m/2-10=-17 | | 6(7-2x)-7=-7 | | −16=4x−2x | | 8z-30=34 | | 1÷7(21c-56)=3(c-8÷3) | | 3=-6-3n | | 2x-x-+9=-6 | | 2x+4=24x+40 | | -5x-16+3x=-9x | | M-20/5-5m-17/7=1 |

Equations solver categories